2022
DOI: 10.3389/fphar.2022.877898
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Protects Neurons in Temporal Lobe Epilepsy and Cognitive Impairment by Repressing Inflammation and Oxidation

Abstract: Temporal lobe epilepsy (TLE) is characterized as an impaired ability of learning and memory with periodic and unpredictable seizures. Status epilepticus (SE) is one of the main causes of TLE. Neuroinflammation and oxidative stress are directly involved in epileptogenesis and neurodegeneration, promoting chronic epilepsy and cognitive deficit. Previous studies have shown that ursolic acid (UA) represses inflammation and oxidative stress, contributing to neuroprotection. Herein, we demonstrated that UA treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Interestingly, UA exhibit significant restoration of the expression levels of these markers in comparison to RA and donepezil (Mirza et al, 2021). It also enhanced neurogenesis and repressed inflammation in temporal lobe epilepsy and cerebral ischemia models Liu et al, 2022). Its role in neurite outgrowth and neuronal survival mediated by nerve growth factor has also been reported (Theis et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, UA exhibit significant restoration of the expression levels of these markers in comparison to RA and donepezil (Mirza et al, 2021). It also enhanced neurogenesis and repressed inflammation in temporal lobe epilepsy and cerebral ischemia models Liu et al, 2022). Its role in neurite outgrowth and neuronal survival mediated by nerve growth factor has also been reported (Theis et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…SE causes hippocampal damage by inducing inflammation, and hippocampal damage eventually leads to chronic TLE. Therefore, epilepsy-induced neuronal damage can be ameliorated through anti-inflammatory effects ( 22 , 43 45 ). Through the continuous study of the TLE mechanism, we can find the target of TLE treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A 2A R Expression in the Rat Hippocampus Some studies have shown that damage to hippocampal neurons can be accompanied by hippocampal inflammation [46][47][48]. TNF-α can induce nerve injury by mediating neuroinflammation and promoting T cells to produce various inflammatory factors [49].…”
Section: Cy Exposure Can Cause Abnormal Changes In the Inflammatory R...mentioning
confidence: 99%